AC/DC rough & tough (Veo Star., 2006)
1. Hells Bells 2. High Voltage 3. Flick Of The Switch 4. What Do You Do For Your Money, Honey 5. Jailbreak 6. Let's Set It Up 7. Show Business 8. Dog Eat Dog 9. Dirty Deeds Done Dirt Cheep 10. Danger 11. Endless Rock - AC/DC Live